2018
DOI: 10.3389/fmicb.2018.01517
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Mycobacterial Inhibitors Against Mycobacterial Protein Kinase G

Abstract: Protein kinase G (PknG) is a eukaryotic-like serine/threonine kinase that is expressed by Mycobacterium tuberculosis and promotes survival of mycobacteria in host macrophages by suppressing phagosome-lysosome fusion. Thus, compounds showing inhibitory activity against PknG are promising anti-mycobacterial agents. We therefore aimed to develop anti-mycobacterial agents by identifying new PknG inhibitors. A luciferase-based PknG kinase assay was used to screen potential inhibitors of PknG. We found that four com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
2
29
0
2
Order By: Relevance
“…These observations are in concordance with the current notion that apoptosis of the infected phagocytes prevents mycobacteria from establishing a suitable niche for long-term survival in the host (45). In agreement, other studies have also identified PknG-specific inhibitors, such as AX20017, aminopyrimidine derivatives, AZD7762, R406, R406f, CYC116, and Sclerotiorin, as promising antimycobacterial agents (31,(48)(49)(50)(51)56). Taken together, we show for the first time that small-molecule targeting of PknD and PknG has no side effects and inhibits bacterial growth in lungs and spleens of infected mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations are in concordance with the current notion that apoptosis of the infected phagocytes prevents mycobacteria from establishing a suitable niche for long-term survival in the host (45). In agreement, other studies have also identified PknG-specific inhibitors, such as AX20017, aminopyrimidine derivatives, AZD7762, R406, R406f, CYC116, and Sclerotiorin, as promising antimycobacterial agents (31,(48)(49)(50)(51)56). Taken together, we show for the first time that small-molecule targeting of PknD and PknG has no side effects and inhibits bacterial growth in lungs and spleens of infected mice.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, it was reported that PknG is secretory in nature and promotes survival of M. tuberculosis in macrophages by inhibiting phagosomelysosome fusion (42)(43)(44). Previous studies have shown that compounds modulating host apoptosis and targeting PknG are promising antimycobacterial agents (31,(44)(45)(46)(47)(48)(49)(50)(51). Since NU-6027 possessed both of these activities, we sought to assess its antimycobacterial activity in THP-1 macrophages infected with either M. bovis BCG or M. tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…Some host-targeting compounds have been demonstrated to possess activity against bacterial kinases, such as the cyclin-dependent kinase 1 inhibitor NU-6027 ( Kidwai et al, 2019 ) and the CHK1 inhibitor AZD7762 ( Kanehiro et al, 2018 ), which inhibit the M.tb kinase, PknG. To examine if DDUG can inhibit bacterial growth in broth, disk diffusion and resazurin assays were conducted, examining a range of pathogenic bacteria and M.tb ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of DDUG against M.tb in broth at concentrations similar to those achieved intracellularly suggests an alternative, CHK2-independent mode of activity. Similarly, the activity of DDUG against some bacteria further suggest DDUG might have promiscuous activity on bacterial kinases, similar to NU-6027 (Kidwai et al, 2019) and AZD7762 (Kanehiro et al, 2018), or otherwise be toxic due to physical properties such as crystallization if concentrated by the macrophage. Conversely, DDUG is not active against M.tb's close family members, M. abscessus and M. bovis-BCG, or Salmonella, which it did inhibit in macrophages, and is active against a small array of seemingly unrelated bacteria ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Another line of currently investigated mycobacterial inhibitors are targeted toward the cytosolic PknG kinase [86,241,242]. In contrast to PknA and PknB, PknG is not essential but is instead important for host intracellular survival by blocking macrophage phago-lysosomal fusion [86].…”
Section: Drugging Bacterial Kinasesmentioning
confidence: 99%